Synchronization of Processes Related to Economic Activity with Stages of Development of Spatially-Organized Systems - Afanasev, Aleksandr Alekseevich; Kasyanov, Vitaliy Fedorovich; Lukmanova, Inessa Galeevna; Silka, Dmitriy Nokolaevich (International Journal of Economics and Financial Issues, 2015)
The development of spatially-organized systems has a cyclic nature characterized by a great number of factors that have a cross-disciplinary character. Herewith, urban planning is presented as a basic direction that ensures the operation of supporting systems. In order to solve the task that arise, the business environment of the urban formation must synchronize with the stages of its development and rise to the existing challenges. For this purpose, in the article the authors consider measures of targeted support for innovation-oriented entrepreneurs with the opportunity to receive rather specific result for the city. Such result is expressed in the formation of the basis of non-material assets that contribute to solving current and strategic tasks of urban planning. Keywords: business, urban planning, geo-informational technologies, economic activity, investments, non-material assets, entrepreneurship. JEL Classifications: O21; R12; R58